2017
DOI: 10.1111/jcpp.12746
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem as a developmental gateway to social attention

Abstract: Background: Evolution preserves social attention due to its key role in supporting survival. Humans are attracted to social cues from infancy, but the neurobiological mechanisms for the development of social attention are unknown. An evolutionary-based, vertical-hierarchical theoretical model of self-regulation suggests that neonatal brainstem inputs are key for the development of well-regulated social attention. Methods: Neonates born preterm (N = 44, GA 34 w.) were recruited and diagnosed at birth as a funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…The link between social function and brainstem neurocircuitry is further supported by the recent findings in both typically developing children and children with ASD. For example, typically developing pre-term neonates who had abnormal ABRs also exhibited deficits in social engagement ( Geva et al, 2013 ), which then developed into impaired social attention at 7–8 years of age ( Geva et al, 2017 ). Concurrently, abnormal ABR of the pre-term neonates who later were diagnosed with ASD predicted the severity of the core autism symptoms such as social and linguistic competence ( Cohen et al, 2013 ).…”
Section: Human Evidence For Brainstem Contributions To Asdmentioning
confidence: 99%
“…The link between social function and brainstem neurocircuitry is further supported by the recent findings in both typically developing children and children with ASD. For example, typically developing pre-term neonates who had abnormal ABRs also exhibited deficits in social engagement ( Geva et al, 2013 ), which then developed into impaired social attention at 7–8 years of age ( Geva et al, 2017 ). Concurrently, abnormal ABR of the pre-term neonates who later were diagnosed with ASD predicted the severity of the core autism symptoms such as social and linguistic competence ( Cohen et al, 2013 ).…”
Section: Human Evidence For Brainstem Contributions To Asdmentioning
confidence: 99%
“…It also plays a pivotal role in sensory information processing, in eliciting goal-oriented behavior, in the regulation of social attention, and in the modulation of emotions (Berntson & Micco, 1976;Geva et al, 2017;Venkatraman, Edlow, & Immordino-Yang, 2017). Structural MRI studies of ASD individuals have demonstrated the potential role of the brainstem in the pathophysiology of ASD (Gaffney, Kuperman, Tsai, & Minchin, 1988) (Jou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…No one has demonstrated essential and consistent evidence of indicators for onset of ASD mainly due to heterogeneity of ASD diagnosis and the possibility of the developing trajectory of the brain and compensatory structural changes [23][24][25]. Some researchers have reported brainstem dysfunction in children with ASD by administrating auditory brainstem evoked responses or by the polyvagal theory [26][27][28].…”
Section: Discussionmentioning
confidence: 99%